Between biodiversity conservation and sustainable forest management – A multidisciplinary assessment of the emblematic Białowieża Forest case. (August 2020) - Blicharska, M.; Angelstam, P.; Giessen, L.; Hilszczański, J.; Hermanowicz, E.; Holeksa, J.; Jacobsen, J.B.; Jaroszewicz, B.; Konczal, A.; Konieczny, A.; Mikusiński, G.; Mirek, Z.; et al.
Abstract: The tension between biodiversity conservation and multipurpose forest management may lead to conflicts. An internationally prominent example is the Białowieża Forest Massif (BFM), an extensive forest complex with high levels of naturalness. We apply a systematic, multidisciplinary assessment process to review empirical evidence on different dimensions of the BFM conflict. While there is broad consensus that this forest massif is an exceptional place worth conserving and that a way forward is a zonation system combining conservation with management, exactly how this should be done has yet to be agreed upon. Our assessment shows that the key reasons for the BFM controversy go beyond the availability of knowledge on the ecological status of the BFM and include: 1) evidence stemming from different sources, which is often contradictory and prone to different interpretations; 2) knowledge gaps, particularly with regard to socio-economic drivers and beneficiaries as well as uncertainties about future trends; 3) fundamentally different values and priorities among stakeholder groups, resulting in power struggles, and an overall lack of trust. We conclude that evidence-based knowledge alone is insufficient to cope with complex conservation conflicts. While more evidence may help assess the consequences of decisions, the actual management decisions depend on different actors' worldviews, which are rooted in their professional identities and power, and their political and legal realities. This calls for conflict management through a well-organized participatory process organized and supervised by a body deemed legitimate by the groups involved.